The role of beef degree of doneness on consumer visual and palatability perceptions - Prill, Lauren L. (Kansas State University, 2019)
The objective of part one was to determine the impact of feeding consumers with varying DOD preferences steaks cooked to multiple DOD on their perceptions of palatability. Paired Low Choice (small⁰⁰ to small¹⁰⁰ marbling) strip loin steaks were used. Each pair of steaks were randomly assigned to a DOD of either rare [60°C (140°F)], medium-rare [63°C (145°F)], medium [71°C (160°F)], medium-well [74°C (165°F)], or well-done [77°C (170°F)]. Consumer panelists were prescreened and assigned to panels based on their DOD preference. In the first round of serving, consumers were served 1 sample from each of the 5 DOD, under low-intensity red incandescent lighting in order to mask any DOD differences among samples. Round 2 consumers were fed under white incandescent lights. There were no consumer preference × steak DOD interactions or consumer preference effects (P > 0.05) for tenderness, juiciness, and flavor when steaks were evaluated under both lighting types. Within the white-light testing, the consumer preference × DOD interaction for overall liking was marginally significant (P = 0.078). Overall, when steaks were overcooked, palatability ratings decreased; however, undercooking had a positive effect on palatability perception, regardless of the consumer’s DOD preference. The objective of part two was to access if published cooking temperatures correlate with DOD. Twenty-four strip loins representing 5 quality treatments were collected. Steaks were cooked to an endpoint temperature of either very rare [55°C (130°F)], rare [60°C (140°F)], medium-rare [63°C (145°F)], medium [71°C (160°F)], well-done [77°C (170°F)], or very well-done [82°C (180°F)]. L*, a*, and b* was evaluated at multiple time points using a Hunter Lab Miniscan spectrophotometer and pictures were taken immediately. A separate digital survey for consumers and chefs was made for the electronic evaluation of the pictures of the cooked steaks. There were time × DOD interactions (P < 0.05) for L*, a*, and b*. For very rare, rare, medium-rare, and medium, a* values increased (P < 0.05) over time. However, for well-done, time only had a minimal impact (P < 0.05) on a* values. When consumers determine DOD cooking beef in their home, they typically use color (54%), a food thermometer (16%), feel or firmness (15.7%) and time (10.4%). Of consumers that utilized a thermometer, 69% reported the temperature they use as their indication of DOD is the temperature they pull off the heat, whereas 31% reported the temperature they use for DOD determination is the temperature following the post-cooking temperature rise. The majority (66%) of chefs reported using feel or firmness for DOD indication, whereas 28% stated they use a thermometer, color (1.2%). There were no quality grade effects (P > 0.05) for any DOD of the steak pictures evaluated by consumers or chefs. Ultimately, consumers were able to accurately match the DOD of the steak pictured to the correct end-point temperature, although this percentage ranged from only 27 to 35%. Additionally, chefs were unable to accurately identify DOD of steaks cooked to specified end-point temperatures. This can create challenges for foodservice establishments to deliver upon consumers DOD preferences.
Keywords: Chef; Degree of doneness; Consumer; Beef; Palatability; Color